Business ethics and social balance: Empirical evidence - Ubaldo Comite; Nadia Oliva (Journal of Contemporary Economic and Business Issues, 2016)
In the past few years a growing consideration of enterprises' social role has brought public opinion, management scholars and companies themselves to give more and more attention and space to the concept of ethics. Over the decades, the doctrine has made some considerable progress in defining that peculiar variation of ethics that is business ethics, while many companies have started to equip themselves with means of measurement and definition of their ethical behavior. Today, indeed, many companies have acquired full knowledge of the fact that it is convenient to manage their ethics as much as their financial efficiency and that it is deeply wrong to believe that committing to managing social relationships is to be considered a mere moral matter (therefore, somehow optional). Today corporations are assigned a new role in society, a role that goes hand in hand with the more 'institutional' one of producing goods and offering services while creating wealth: this way, the company becomes an organization which must acquire a more responsible behavior in the satisfaction of human rights. It becomes a cell operating in synergy in the vaster macroeconomics system. The aim of this paper is to show the dynamics that exist between business ethics and social balance.
Keywords: M1; M10; M14; 330; ethics; company; social balance; corporate social responsibility; sustainability; moral choices; values; profit